HUBUNGAN DUKUNGAN KELUARGA DENGAN PEMBERIAN ASI EKSKLUSIF PADA BAYI UMUR 6-12 BULAN DI DESA BUJAK KECAMATAN BATUKLIANG KABUPATEN LOMBOK TENGAH - Fuji Khairani; Ismiati; Dita Retno Pratiwi (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Children are every family's dream. Exclusive breastfeeding is the best investment for children's health and intelligence. Exclusive breastfeeding is influenced by health behavior factors, one of which is the driving factor including the support of husband and family which is very necessary so that mothers can breastfeed exclusively. Support or support from other people or those closest to you plays a big role in the success or failure of providing exclusive breastfeeding. Objective: The aim of the research is to determine the relationship between family support and exclusive breastfeeding for babies aged 6-12 months in Bujak Village, Batukliang District, Lombok Regency. Middle. Research Method: analytical research with a Cross Sectional Study approach, using Simple Random Sampling techniques with a total of 83 toddlers. Research Results: The results of hypothesis testing using the Chi Square test at a confidence level of 95% (α=0.05%), show that there is a relationship between family support and exclusive breastfeeding for babies where the p value=0.000 is smaller than 0.05%. Conclusion: There is a relationship between family support and exclusive breastfeeding for babies aged 6-12 months. It was found that most respondents received good family support for exclusive breastfeeding, so there is a significant relationship between family support and exclusive breastfeeding for babies.